PEM water electrolysis hydrogen production gas diffusion layer and preparation method thereof

By adopting two layers of titanium materials with different pores in the anode gas diffusion layer of the PEM hydrolysis cell, the problem of low catalyst utilization rate and large load capacity in existing technologies can be solved. Reduced the efficiency of PEM electrolytic hydrogenation and reduced costs.

CN119372676APending Publication Date: 2025-01-28NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH

Patent Information

Application Number
CN202411512245.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The anode gas diffusion layer material of the existing PEM water electrolytic cells is prone to corrosion under high oxygen analysis potential and acidic environment, resulting in low catalyst utilization and large load, limiting battery efficiency.

Method used

The titanium gas diffusion layer with different pores with different pores, titanium micro -pores close to the reaction site with a smaller pore diameter to increase the utilization rate of catalyst, and the titanium base layer away from the reaction site has a large pore diameter to facilitate gas entry. Realize efficient gas transmission.

Benefits of technology

While ensuring the efficiency of gas fluid transmission, effectively reduce the load of catalysts, improve the efficiency of PEM electrolytic hydrogenation and reduce costs, and meet the needs of recalculating energy and PEM hydrolysis of hydrogen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372676A_ABST
    Figure CN119372676A_ABST
Patent Text Reader

Abstract

The invention discloses a PEM gas diffusion layer for hydrogen production by electrolyzing water, the gas diffusion layer is formed by metallurgical bonding of a titanium microporous layer and a titanium substrate layer, the total thickness of the gas diffusion layer is 110-490 [mu] m, the thickness of the titanium microporous layer is 10-100 [mu] m, the average aperture of the titanium microporous layer is 1-8 [mu] m, the thickness of the titanium substrate layer is 100-480 [mu] m, the average aperture of the titanium substrate layer is 10-25 [mu] m, and the thickness of the titanium substrate layer is 10-30 [mu] m. The invention also discloses a preparation method of the gas diffusion layer, which comprises the following steps: pressing titanium powder to obtain a green body thin strip, then spraying slurry on the green body thin strip, and finally degreasing and sintering. The pore diameter of the titanium substrate layer is regulated and controlled by controlling the particle size of the titanium powder, the feeding speed and the rotating speed of the roller, the pore diameter of the titanium microporous layer is regulated and controlled by controlling the slurry ratio, the particle size of the small-particle titanium powder and the pressure of the spray gun, and the gas diffusion layer for PEM water electrolysis hydrogen production, which ensures the gas-liquid transmission efficiency and effectively reduces the catalyst loading capacity, can be prepared only through one-step sintering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen production by water electrolysis, and specifically relates to a gas diffusion layer for hydrogen production by water electrolysis by PEM and a preparation method thereof. Background Art

[0002] The gas diffusion layer is the core component of the proton exchange membrane (PEM) water electrolysis hydrogen production device. Its materials, structure, design and preparation play a key role in further improving the performance and efficiency of electrolysis hydrogen production and reducing costs. On the anode side, water enters the membrane electrode surface through the gas diffusion layer for decomposition reaction, releasing oxygen molecules, protons and electrons. Due to the acidic environment in the PEM water electrolysis cell, the applied voltage is generally higher than 1.5V, the high oxygen evolution potential, the oxidizing active oxygen generated during water electrolysis, and the chemical and electrochemical corrosion in the acidic environment, the traditional carbon materials (carbon paper, carbon cloth) and ordinary metal materials (stainless steel felt, nickel mesh, etc.) used in fuel cells are no longer suitable for anode gas diffusion layer materials. At present, titanium with good corrosion resistance is generally selected as the diffusion layer material of the PEM water electrolysis cell. Among them, powder sintered porous titanium has become one of the products with the most development potential due to its advantages such as high mechanical stability, high controllability of pore structure and good conductivity.

[0003] Studies have shown that the interface structure between the anode porous titanium gas diffusion layer and the catalyst layer is a key factor limiting battery efficiency. Although high porosity can ensure good gas-liquid transmission, it will lead to a reduction in contact points with the catalyst layer, reduce catalyst utilization, and increase its loading. Therefore, it is urgent to optimize the interface structure of the direct contact between the two and explore a reasonable and efficient method to successfully prepare a porous titanium gas diffusion layer that can effectively reduce the catalyst loading while ensuring gas-liquid transmission efficiency, thereby meeting the development needs of high-efficiency and low-cost hydrogen production by coupling renewable energy with PEM water electrolysis. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a gas diffusion layer for hydrogen production by PEM water electrolysis in view of the deficiencies of the above-mentioned prior art. The gas diffusion layer is set as a two-layer structure with different pore sizes. The titanium microporous layer with a smaller pore size can ensure that the gas and the catalyst have sufficient contact opportunities, improve the utilization rate of the catalyst, and the titanium substrate layer with a larger pore size can make it easier for the gas to enter the gas diffusion layer, and guide the gas to quickly enter the gas diffusion layer from a macroscopic perspective, which is conducive to the efficient transmission of gas during PEM water electrolysis to produce hydrogen, and ensures the gas-liquid transmission efficiency while effectively reducing the catalyst loading, meeting the development needs of high-efficiency and low-cost hydrogen production coupled with renewable energy and PEM water electrolysis.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a gas diffusion layer for PEM water electrolysis to produce hydrogen, characterized in that the gas diffusion layer is formed by metallurgical bonding of two titanium microporous layers with different pore sizes and a titanium substrate layer, the total thickness of the gas diffusion layer is 110μm to 490μm, the thickness of the titanium microporous layer is 10μm to 100μm, the average pore size is 1μm to 8μm, the thickness of the titanium substrate layer is 100μm to 480μm, and the average pore size is 10μm to 25μm.

[0006] The present invention sets the gas diffusion layer as a two-layer structure with different pore sizes. When PEM water electrolysis produces hydrogen, the titanium microporous layer with smaller pore size on the side close to the reaction site can ensure that the gas and the catalyst have sufficient contact opportunities, thereby improving the utilization rate of the catalyst. On the side away from the reaction site, the titanium substrate layer with larger pore size can make it easier for the gas to enter the gas diffusion layer, and macroscopically guide the gas to quickly enter the gas diffusion layer, which is helpful for the efficient transmission of the gas when PEM water electrolysis produces hydrogen, ensures the gas-liquid transmission efficiency, and effectively reduces the catalyst loading, thereby meeting the development needs of high-efficiency and low-cost hydrogen production coupled with renewable energy and PEM water electrolysis.

[0007] The above-mentioned gas diffusion layer for PEM water electrolysis hydrogen production is characterized in that the titanium microporous layer is a multilayer structure, the pore size of each layer in the multilayer structure changes in a gradient, and the pore size far away from the titanium substrate layer is small, and the pore size close to the titanium substrate layer is large. The present invention further subdivides the titanium microporous layer into a multilayer structure with a gradient pore size, so that the gas diffusion layer acts as a funnel, further improves the efficient transmission of gas, ensures the gas-liquid transmission efficiency, and effectively reduces the catalyst loading, meeting the development needs of high-efficiency and low-cost hydrogen production by coupling renewable energy with PEM water electrolysis.

[0008] In addition, the present invention also provides a method for preparing a gas diffusion layer for PEM water electrolysis hydrogen production, characterized in that the method comprises the following steps:

[0009] Step 1: Feed titanium powder with a powder size of 75 μm to 150 μm into two counter-rotating rollers, press and lead out to form a green strip;

[0010] Step 2: dissolving polyvinyl butyral powder in anhydrous ethanol to form a uniform solution, then adding small-particle titanium powder thereto and mixing uniformly to form a slurry, and spraying the slurry onto the surface of the green strip obtained in step 1 at a pressure of 0.1 MPa to 0.5 MPa using a spray gun to obtain a sprayed green strip;

[0011] Step 3: When the vacuum degree is not greater than 1×10 -2Pa, the sprayed green strip obtained in step 2 is heated to 300°C~550°C at a heating rate of 0.5°C / min~4°C / min, degreased for 2h~7h, then immediately heated to 800°C~1150°C at a heating rate of 2°C / min~7°C / min, sintered for 0.5h~3h, and finally furnace cooled to room temperature to obtain a gas diffusion layer for PEM water electrolysis to produce hydrogen.

[0012] The present invention ensures that the pore size of the titanium substrate layer is 10 to 25 μm by controlling the particle size of the titanium powder and matching the subsequent sintering temperature and time; adds polyvinyl butyral to adjust the viscosity of the slurry so that the slurry has suitable fluidity and improves the spraying effect; controls the pressure of the spray gun and the weight of the small-particle titanium powder sprayed from the spray gun per unit time, thereby ensuring that the thickness of the titanium microporous layer is 10 to 100 μm; ensures that the polyvinyl butyral and anhydrous ethanol are completely removed by heating and degreasing in the first stage; and metallurgically combines the titanium microporous layer and the titanium substrate layer by heating and sintering in the second stage, and controls the shrinkage degree in the powder sintering process to avoid warping of the gas diffusion layer and affecting product quality.

[0013] The above method is characterized in that the feeding speed of the titanium powder in step 1 is 70g / s to 120g / s, and the rotation speeds of the two rollers are both 30r / min to 70r / min. In the present invention, the feeding speed of the titanium powder and the rotation speed of the rollers are controlled in accordance with the particle size of the titanium powder, and the amount of powder bite during the pressing process is strictly controlled, thereby ensuring that the thickness of the green strip is 100μm to 480μm.

[0014] The above method is characterized in that the concentration of polyvinyl butyral in the slurry in step 2 is 0.02g / mL to 0.1g / mL, and the concentration of small-particle titanium powder in the slurry is 0.3g / mL to 2g / mL. The present invention controls the weight of small-particle titanium powder sprayed from the spray gun per unit time by controlling the concentration of polyvinyl butyral and small-particle titanium powder and coordinating the pressure of the spray gun, thereby ensuring that the thickness of the titanium microporous layer is 10μm to 100μm, and under the same other conditions, within a certain range, the higher the concentration of polyvinyl butyral, the greater the amount of powder sprayed, and vice versa. If it is too high, it may cause the slurry fluidity to be too low, the spray gun to be blocked, and the amount of sprayed powder to be sharply reduced or even unable to be sprayed, so the concentration of polyvinyl butyral in the slurry is controlled to be 0.02g / mL to 0.1g / mL.

[0015] The above method is characterized in that the particle size of the small-particle titanium powder in step 2 is 2 μm to 30 μm. The present invention ensures that the pore size of the titanium microporous layer is 1 μm to 8 μm by controlling the particle size of the small-particle titanium powder and coordinating the sintering temperature and time in step 3.

[0016] The above method is characterized in that step 2 and step 3 are repeated multiple times. In the present invention, step 2 and step 3 are repeated once, that is, one layer of titanium microporous layer is added to form two titanium microporous layers. By repeating step 2 and step 3 multiple times to form a multi-layer titanium microporous layer, the efficient transmission of gas is further improved.

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] 1. The present invention sets the gas diffusion layer as a two-layer structure with different pore sizes. When PEM water electrolysis produces hydrogen, the titanium microporous layer with smaller pore size on the side close to the reaction site can ensure that the gas and the catalyst have sufficient contact opportunities, thereby improving the utilization rate of the catalyst. On the side away from the reaction site, the titanium substrate layer with larger pore size can make it easier for the gas to enter the gas diffusion layer, and guide the gas to quickly enter the gas diffusion layer from a macroscopic perspective, which is helpful for the efficient transmission of gas when PEM water electrolysis produces hydrogen, ensures the gas-liquid transmission efficiency, and effectively reduces the catalyst loading, thereby meeting the development needs of high-efficiency and low-cost hydrogen production coupled with renewable energy and PEM water electrolysis.

[0019] 2. The present invention controls the particle size of titanium powder and coordinates the subsequent sintering temperature and time to ensure that the pore size of the titanium substrate layer is 10μm to 25μm; adds polyvinyl butyral to adjust the viscosity of the slurry so that the slurry has suitable fluidity and improves the spraying effect; controls the pressure of the spray gun and the weight of small-particle titanium powder sprayed from the spray gun per unit time to ensure that the thickness of the titanium microporous layer is 10μm to 100μm; through the first stage of heating degreasing, it is ensured that polyvinyl butyral and anhydrous ethanol are completely removed; through the second stage of heating sintering, the titanium microporous layer and the titanium substrate layer are metallurgically bonded, and at the same time, the shrinkage degree of the powder during sintering is controlled to avoid warping of the gas diffusion layer and affecting product quality.

[0020] 3. The present invention controls the particle size of titanium powder, the feeding speed and the roller speed. The combination of the three can strictly control the amount of powder bite during the rolling process, thereby ensuring that the thickness of the green thin strip is 100μm to 480μm. By controlling the particle size of titanium powder and coordinating the sintering temperature and time, the pore size of the titanium substrate layer is ensured to be 10μm to 25μm.

[0021] 4. The present invention controls the concentration of polyvinyl butyral and small-particle titanium powder in the slurry and coordinates the spray gun pressure to control the weight of titanium powder sprayed from the spray gun per unit time, thereby ensuring that the thickness of the titanium microporous layer is 10μm to 100μm. By controlling the particle size of the small-particle titanium powder and coordinating the sintering temperature and time, the pore size of the titanium microporous layer is ensured to be 1μm to 8μm.

[0022] 5. The present invention sprays a titanium microporous layer on the surface of a green sheet, and only requires one step of sintering to prepare a gas diffusion layer for hydrogen production by electrolysis of water in PEM, with high production efficiency.

[0023] 6. Steps 2 and 3 of the present invention can be repeated multiple times to prepare a gas diffusion layer for PEM water electrolysis hydrogen production having a gradient pore structure (the total number of microporous layers and substrate layers is ≥ 3), further improving the efficient gas transmission effect, ensuring the gas-liquid transmission efficiency while effectively reducing the catalyst loading, and meeting the development needs of high-efficiency and low-cost hydrogen production by coupling renewable energy with PEM water electrolysis.

[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a microstructure diagram of the gas diffusion layer for PEM water electrolysis hydrogen production prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] Example 1

[0027] This embodiment includes the following steps:

[0028] Step 1: feeding titanium powder with a powder particle size of 100 μm to 125 μm into two rollers rotating at 35 r / min in opposite directions at a speed of 72 g / s, pressing and leading out to form a green strip;

[0029] Step 2: dissolving polyvinyl butyral powder in anhydrous ethanol to form a uniform solution, adding small-particle titanium powder with a particle size of 10 μm to 20 μm thereto and mixing them evenly to form a slurry, wherein the concentration of polyvinyl butyral in the slurry is 0.06 g / mL, and the concentration of titanium powder in the slurry is 1.1 g / mL, and the slurry is sprayed onto the surface of the green strip obtained in step 1 with a spray gun at a pressure of 0.3 MPa to obtain a sprayed green strip;

[0030] Step 3: At a vacuum degree of 8.3×10 -3 Pa, the sprayed green strip obtained in step 2 was heated to 400°C at a heating rate of 2°C / min and kept warm for 4 hours, then immediately heated to 1000°C at a heating rate of 5°C / min and kept warm for 1.5 hours, and finally furnace cooled to room temperature to obtain a gas diffusion layer for PEM water electrolysis to produce hydrogen.

[0031] After testing, the gas diffusion layer for PEM water electrolysis hydrogen production prepared in this embodiment has a total thickness of 370 μm, of which the titanium microporous layer has a thickness of 85 μm and an average pore size of 8 μm, and the titanium substrate layer has a thickness of 285 μm and an average pore size of 17 μm.

[0032] Figure 1 is a microstructure diagram of the gas diffusion layer for hydrogen production by PEM electrolysis of water prepared in this embodiment. Figure 1 It can be seen that the titanium microporous layer and the titanium substrate layer form a good metallurgical bond.

[0033] Example 2

[0034] This embodiment includes the following steps:

[0035] Step 1: titanium powder with a powder size of 75 μm to 120 μm is fed into two rollers rotating at 70 r / min in opposite directions at a speed of 72 g / s, and is pressed and led out to form a green strip;

[0036] Step 2: dissolving polyvinyl butyral powder in anhydrous ethanol to form a uniform solution, adding small-particle titanium powder with a particle size of 10 μm to 20 μm thereto and mixing them evenly to form a slurry, wherein the concentration of polyvinyl butyral in the slurry is 0.1 g / mL, and the concentration of titanium powder in the slurry is 0.5 g / mL, and the slurry is sprayed onto the surface of the green strip obtained in step 1 with a spray gun at a pressure of 0.3 MPa to obtain a sprayed green strip;

[0037] Step 3: At a vacuum degree of 8.3×10 -3 Pa, the sprayed green strip obtained in step 2 was heated to 400°C at a heating rate of 2°C / min and kept warm for 4 hours, then immediately heated to 1000°C at a heating rate of 5°C / min and kept warm for 1.5 hours, and finally furnace cooled to room temperature to obtain a gas diffusion layer for PEM water electrolysis to produce hydrogen.

[0038] After testing, the gas diffusion layer for PEM water electrolysis hydrogen production prepared in this embodiment has a total thickness of 120 μm, of which the titanium microporous layer has a thickness of 15 μm and an average pore size of 2 μm, and the titanium substrate layer has a thickness of 105 μm and an average pore size of 11 μm.

[0039] Example 3

[0040] This embodiment includes the following steps:

[0041] Step 1: feeding titanium powder with a powder particle size of 100 μm to 150 μm into two rollers rotating at a speed of 35 r / min in opposite directions at a speed of 120 g / s, pressing and leading out to form a green strip;

[0042] Step 2: dissolving polyvinyl butyral powder in anhydrous ethanol to form a uniform solution, adding small-particle titanium powder with a particle size of 2 μm to 10 μm thereto and mixing them evenly to form a slurry, wherein the concentration of polyvinyl butyral in the slurry is 0.02 g / mL, and the concentration of titanium powder in the slurry is 0.3 g / mL, and the slurry is sprayed onto the surface of the green strip obtained in step 1 with a spray gun at a pressure of 0.3 MPa to obtain a sprayed green strip;

[0043] Step 3: At a vacuum degree of 8.3×10 -3 Pa, the sprayed green strip obtained in step 2 was heated to 400°C at a heating rate of 2°C / min and kept warm for 4 hours, then immediately heated to 1000°C at a heating rate of 5°C / min and kept warm for 1.5 hours, and finally furnace cooled to room temperature to obtain a gas diffusion layer for PEM water electrolysis to produce hydrogen.

[0044] After testing, the gas diffusion layer for PEM water electrolysis hydrogen production prepared in this embodiment has a total thickness of 470 μm, of which the titanium microporous layer has a thickness of 70 μm and an average pore size of 4 μm, and the titanium substrate layer has a thickness of 400 μm and an average pore size of 24 μm.

[0045] Example 4

[0046] This embodiment includes the following steps:

[0047] Step 1: feeding titanium powder with a powder particle size of 100 μm to 125 μm into two rollers rotating at 35 r / min in opposite directions at a speed of 70 g / s, pressing and leading out to form a green strip;

[0048] Step 2: dissolving polyvinyl butyral powder in anhydrous ethanol to form a uniform solution, adding small-particle titanium powder with a particle size of 20 μm to 30 μm thereto and mixing them evenly to form a slurry, wherein the concentration of polyvinyl butyral in the slurry is 0.02 g / mL, and the concentration of titanium powder in the slurry is 0.3 g / mL, and the slurry is sprayed onto the surface of the green strip obtained in step 1 with a spray gun at a pressure of 0.1 MPa to obtain a sprayed green strip;

[0049] Step 3: At a vacuum degree of 8.3×10 -3 Pa, the sprayed green strip obtained in step 2 was heated to 550°C at a heating rate of 4°C / min and kept warm for 7 hours, then immediately heated to 1150°C at a heating rate of 7°C / min and kept warm for 3 hours, and finally furnace cooled to room temperature to obtain a gas diffusion layer for PEM water electrolysis to produce hydrogen.

[0050] After testing, the gas diffusion layer for PEM water electrolysis hydrogen production prepared in this embodiment has a total thickness of 320 μm, of which the titanium microporous layer has a thickness of 40 μm and an average pore size of 7 μm, and the titanium substrate layer has a thickness of 280 μm and an average pore size of 18 μm.

[0051] Example 5

[0052] This embodiment includes the following steps:

[0053] Step 1: feeding titanium powder with a powder particle size of 100 μm to 125 μm into two rollers rotating at a speed of 30 r / min in opposite directions at a speed of 72 g / s, pressing and leading out to form a green strip;

[0054] Step 2: dissolving polyvinyl butyral powder in anhydrous ethanol to form a uniform solution, adding small-particle titanium powder with a particle size of 2 μm to 10 μm thereto and mixing them evenly to form a slurry, wherein the concentration of polyvinyl butyral in the slurry is 0.02 g / mL, and the concentration of titanium powder in the slurry is 0.3 g / mL, and the slurry is sprayed onto the surface of the green strip obtained in step 1 with a spray gun at a pressure of 0.5 MPa to obtain a sprayed green strip;

[0055] Step 3: At a vacuum degree of 8.3×10 -3 Pa, the sprayed green strip obtained in step 2 was heated to 300°C at a heating rate of 0.5°C / min and kept warm for 2h, then immediately heated to 800°C at a heating rate of 2°C / min and kept warm for 0.5h, and finally furnace cooled to room temperature to obtain a gas diffusion layer for PEM water electrolysis to produce hydrogen.

[0056] After testing, the gas diffusion layer for PEM water electrolysis hydrogen production prepared in this embodiment has a total thickness of 380 μm, of which the titanium microporous layer has a thickness of 98 μm and an average pore size of 3 μm, and the titanium substrate layer has a thickness of 282 μm and an average pore size of 12 μm.

[0057] Example 6

[0058] This embodiment includes the following steps:

[0059] Step 1: feeding titanium powder with a powder particle size of 100 μm to 125 μm into two rollers rotating at a speed of 30 r / min in opposite directions at a speed of 72 g / s, pressing and leading out to form a green strip;

[0060] Step 2: dissolving polyvinyl butyral powder in anhydrous ethanol to form a uniform solution, adding small-particle titanium powder with a particle size of 2 μm to 10 μm thereto and mixing them evenly to form a slurry, wherein the concentration of polyvinyl butyral in the slurry is 0.02 g / mL, and the concentration of titanium powder in the slurry is 0.3 g / mL, and the slurry is sprayed onto the surface of the green strip obtained in step 1 with a spray gun at a pressure of 0.5 MPa to obtain a sprayed green strip;

[0061] Step 3: At a vacuum degree of 8.3×10 -3 Pa, the sprayed green sheet obtained in step 2 was heated to 300°C at a heating rate of 0.5°C / min and kept at that temperature for 2h, then immediately heated to 800°C at a heating rate of 2°C / min and kept at that temperature for 0.5h, and finally furnace cooled to room temperature;

[0062] Step 4: Perform step 2 and step 3 again, add small-particle titanium powder with a particle size of 2 μm to 5 μm in step 2, and set the spray gun pressure to 0.1 MPa to obtain a gas diffusion layer for PEM water electrolysis to produce hydrogen.

[0063] After testing, the gas diffusion layer for PEM water electrolysis to produce hydrogen prepared in this embodiment has a total thickness of 394μm, of which the titanium microporous layer is two layers. The thickness of the titanium microporous layer close to the titanium substrate layer is 20μm and the average pore size is 1μm, the thickness of the titanium microporous layer far away from the titanium substrate layer is 96μm and the average pore size is 3μm, and the thickness of the titanium substrate layer is 278μm and the average pore size is 16μm.

[0064] Example 7

[0065] This embodiment includes the following steps:

[0066] Step 1: feeding titanium powder with a powder size of 100 μm to 150 μm into two rollers rotating at a speed of 40 r / min in opposite directions at a speed of 100 g / s, pressing and leading out to form a green strip;

[0067] Step 2: dissolving polyvinyl butyral powder in anhydrous ethanol to form a uniform solution, adding small-particle titanium powder with a particle size of 10 μm to 20 μm thereto and mixing them evenly to form a slurry, wherein the concentration of polyvinyl butyral in the slurry is 0.1 g / mL, and the concentration of titanium powder in the slurry is 0.5 g / mL, and the slurry is sprayed onto the surface of the green strip obtained in step 1 with a spray gun at a pressure of 0.3 MPa to obtain a sprayed green strip;

[0068] Step 3: At a vacuum degree of 8.3×10 -3Pa, the sprayed green strip obtained in step 2 was heated to 400°C at a heating rate of 2°C / min and kept warm for 4 hours, then immediately heated to 1000°C at a heating rate of 5°C / min and kept warm for 1.5 hours, and finally furnace cooled to room temperature to obtain a gas diffusion layer for PEM water electrolysis to produce hydrogen.

[0069] After testing, the gas diffusion layer for PEM water electrolysis hydrogen production prepared in this embodiment has a total thickness of 490 μm, of which the titanium microporous layer has a thickness of 10 μm and an average pore size of 2 μm, and the titanium substrate layer has a thickness of 480 μm and an average pore size of 11 μm.

[0070] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent changes made to the above embodiments according to the technical essence of the present invention still fall within the protection scope of the technical solution of the present invention.

Claims

1. A gas diffusion layer for PEM water electrolysis to produce hydrogen, characterized in that: The gas diffusion layer is formed by metallurgically bonding two titanium microporous layers with different pore sizes and a titanium substrate layer. The total thickness of the gas diffusion layer is 110 μm to 490 μm, the thickness of the titanium microporous layer is 10 μm to 100 μm, and the average pore size is 1 μm to 8 μm. The thickness of the titanium substrate layer is 100 μm to 480 μm, and the average pore size is 10 μm to 25 μm.

2. A gas diffusion layer for producing hydrogen by PEM electrolysis of water according to claim 1, characterized in that: The titanium microporous layer is a multi-layer structure, and the pore size of each layer in the multi-layer structure changes in a gradient, and the pore size far away from the titanium substrate layer is small, and the pore size close to the titanium substrate layer is large.

3. A method for preparing a gas diffusion layer for hydrogen production by PEM water electrolysis as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: Step 1: Feed titanium powder with a powder size of 75 μm to 150 μm into two counter-rotating rollers, press and lead out to form a green strip; Step 2: dissolving polyvinyl butyral powder in anhydrous ethanol to form a uniform solution, then adding small-particle titanium powder thereto and mixing uniformly to form a slurry, and spraying the slurry onto the surface of the green strip obtained in step 1 at a pressure of 0.1 MPa to 0.5 MPa using a spray gun to obtain a sprayed green strip; Step 3: When the vacuum degree is not greater than 1×10 -2 Pa, the sprayed green strip obtained in step 2 is heated to 300°C~550°C at a heating rate of 0.5°C / min~4°C / min, degreased for 2h~7h, then immediately heated to 800°C~1150°C at a heating rate of 2°C / min~7°C / min, sintered for 0.5h~3h, and finally furnace cooled to room temperature to obtain a gas diffusion layer for PEM water electrolysis to produce hydrogen.

4. The method according to claim 3, characterized in that The feeding speed of the titanium powder in step 1 is 70 g / s to 120 g / s, and the rotation speeds of the two rollers are both 30 r / min to 70 r / min.

5. The method according to claim 3, characterized in that: In step 2, the concentration of polyvinyl butyral in the slurry is 0.02 g / mL to 0.1 g / mL, and the concentration of the small-particle titanium powder in the slurry is 0.3 g / mL to 2 g / mL.

6. The method according to claim 3, characterized in that The particle size of the small-particle titanium powder in step 2 is 2 μm to 30 μm.

7. The method according to claim 3, characterized in that Repeat steps 2 and 3 several times.

Citation Information

Patent Citations

  • Porous metal-ceramic composite material gas spreading layer used for hydrogen fuel cell and preparation method thereof

    CN102810680A

  • Manufacturing method of gas diffusion layer with microporous layer, and manufacturing method of fuel cell

    CN112952110A

  • Powder composite gas diffusion layer and preparation method and application thereof

    CN115642262A

  • PEM electrolytic hydrogen production cathode diffusion layer and preparation method thereof

    CN117026272A

  • Method for producing porous transport layer

    CN118119466A

Cited By

  • Gas diffusion layer with gradient pore structure and preparation method thereof

    CN120844109A

  • Preparation method of low-roughness microporous material, microporous material and application of microporous material

    CN122298991A